Impact of investing in new port capacity from a shipper and a shipowner perspective: The case of maasvlakte II. Issue 4 (December 2020) - van Hassel, Edwin; Meersman, Hilde; Van de Voorde, Eddy; Vanelslander, Thierry
Highlights: Investments into the new port capacity should be evaluated as long run investments. The availability of having free capacity should be considered as a benefit when evaluating investments in new port capacity. Additional free capacity will contribute to increasing the competitive position of the port. Abstract: In this contribution, the effect of implementing the Rotterdam Maasvlakte II terminal is researched both from a shipper and from a shipowner perspective. More in particular, four scenarios are analysed: two scenarios in which the impact of opening Maasvlakte II is researched and two scenarios in which Maasvlakte II is assumed not to exist. In these latter two scenarios, the effect of potential congestion is calculated. For the calculations, we use a model which is able to calculate the total generalised chain cost for a supply chain. The calculations show that the impact on the total chain cost (the shipper's perspective) of starting to use Maasvlakte II is rather limited. The congestion levels at Maasvlakte I (in 2012) were not so high that they caused a significant increase of the total chain cost. When it comes to the vessel cost in a port (the shipowner's perspective), the total vessel cost increases rapidly because not the cost per TEU is relevant but rather the total cost of the vessel. Shipowners design the loop in such a way that it can offer the smallest generalised chain cost to their customers (the shippers) and also allows minimising their own cost. If Maasvlakte II were not built, the container throughput of the port of Rotterdam would not have been able to increase, without having heavy congestion. The excess growth would then have been absorbed mainly by the port of Antwerp. Therefore, the investments into the new Maasvlakte II in Rotterdam, as well as other port investment projects, should be evaluated as (very) long run investments.